Full Digital Surgery-First, Skeletal Anchorage and Aligners Approach to Correct a Gummy Smile and Class II Malocclusion with Mandibular Retrusion and Deviation - Giorgio Iodice; Gianpaolo Tartaro; Mario Santagata; Salvatore D’Amato (Applied Sciences, 2021)
Background: The demand for interdisciplinary orthodontic treatment has increased significantly in the past few years, especially in adult patients. This kind of treatment requires careful clinical management, as consequence of the possible complications and limits related to adult age. However, the use of skeletal anchorage and three-dimensional (3D) digital technology has deeply revolutionised diagnostic planning and treatment strategies. Methods: A fully digital approach to the treatment of a Class II patient with a gummy smile and mandibular deficiency and deviation, consisting of initial surgery followed by the use of aligners and skeletal anchorage, is described. Results: The 3D, fully digital pre-evaluation enabled clinicians to accurately and reliably plan the surgical procedure and subsequent orthodontics, including the individualised positioning of stabilisation plates and a splint for maxillary and chin surgical movements. This allowed for the improvement of the patient’s facial aesthetics and dental occlusion without the use of visible orthodontic appliances or the occurrence of pre-surgical aesthetic worsening. Conclusions: This approach could be very effective for adult patients seeking aesthetic treatment options for facial and dental aesthetic improvement.